Plant Biotic and Abiotic Stresses Volume II - Manghwar, Hakim; Zaman, Wajid (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plants under natural conditions often face multiple stresses, including drought, salinity, temperature extremes, submergence stress, bacteria, viruses, fungi, insects, etc. These biotic and abiotic stresses negatively influence plant growth and productivity. Various approaches have recently been used to overcome stresses in plants. It is necessary to evaluate and explore how diverse molecular techniques can be applied to different biological studies to improve biotic and abiotic stress tolerance in plants. This will help reduce production losses and increase crop tolerance to various stresses. It is now the time to make a difference by developing plants that can withstand biotic and abiotic stresses.